2008
DOI: 10.1093/molbev/msn281
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Primate Orphan Genes: A Comparative Genomics Approach

Abstract: Genomes contain a large number of genes that do not have recognizable homologues in other species and that are likely to be involved in important species-specific adaptive processes. The origin of many such "orphan" genes remains unknown. Here we present the first systematic study of the characteristics and mechanisms of formation of primate-specific orphan genes. We determine that codon usage values for most orphan genes fall within the bulk of the codon usage distribution of bona fide human proteins, support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
260
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(295 citation statements)
references
References 61 publications
30
260
1
Order By: Relevance
“…Prior to this study, there were few reports of novel gene origination by this mechanism and none identified human-specific genes (Levine et al 2006;Begun et al 2007;Cai et al 2008;Zhou et al 2008;Toll-Riera et al 2009). The novel proteins identified in this study are all short, encoded by an uninterrupted ORF, are supported by expression data, and the corresponding regions of chromosome where the ortholog is expected to be found in chimp and macaque harbor disabling mutations, which mean that the protein cannot be produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this study, there were few reports of novel gene origination by this mechanism and none identified human-specific genes (Levine et al 2006;Begun et al 2007;Cai et al 2008;Zhou et al 2008;Toll-Riera et al 2009). The novel proteins identified in this study are all short, encoded by an uninterrupted ORF, are supported by expression data, and the corresponding regions of chromosome where the ortholog is expected to be found in chimp and macaque harbor disabling mutations, which mean that the protein cannot be produced.…”
Section: Discussionmentioning
confidence: 99%
“…New genes frequently arise through duplication of existing genes, or through fusion, fission, or exon shuffling between genes (Long et al 2003). Origination of genes from noncoding DNA is extremely rare: A few eukaryotic examples are known in yeast and Drosophila (Levine et al 2006;Begun et al 2007;Cai et al 2008;Zhou et al 2008) and a very recent paper reported initial evidence for this process in a primate ancestor (Toll-Riera et al 2009). No cases have been previously reported in human.…”
mentioning
confidence: 99%
“…These young genes were found to evolve very rapidly, showing a median of 47.3% divergence, at the amino-acid level, from their parents. In an analysis of the mechanisms of formation of primate-specific genes, we observed that about 24% of the newly formed genes had originated through gene duplication, frequently involving partial gene duplication and the recruitment of additional sequences (Toll-Riera et al, 2009a). One example is human XAGE-1, a cancer/testis-associated gene that has partial homology to human XAGE-2, a gene that is well conserved in other mammals.…”
Section: Partial Gene Duplicationmentioning
confidence: 99%
“…In contrast, lineagespecific genes (LSGs), which are also referred to as taxonomically restricted genes that share no sequence similarity with genes of other lineages in one taxonomic group [2][3][4][5][6][7][8], are often ignored in genomics. However, study of these genes is helpful to aid in the comprehensive understanding of a species.…”
Section: Introductionmentioning
confidence: 99%
“…However, study of these genes is helpful to aid in the comprehensive understanding of a species. With the increasing development of sequencing technologies, we have gained access to a number of genomes and transcriptomes from a wide range of species, which has aided the extensive study of the LSGs within mammals [8][9][10], insects [2,11,12], fish [13], plants [5,[14][15][16], and microbial species [17][18][19][20]. However, the LSGs in C. elegans have not yet been researched through genomewide methods.…”
Section: Introductionmentioning
confidence: 99%